Arctic climate change : The ACSYS decade and beyond - Jacobi, Hans-Werner; Lemke, Peter (Atmospheric and Oceanographic Sciences Library, 2012)
The Arctic is now experiencing some of the most rapid and severe climate change on earth. Over the next 100 years, climate change is expected to accelerate, contributing to major physical, ecological, social, and economic changes, many of which have already begun. Changes in arctic climate will also affect the rest of the world through increased global warming and rising sea levels. The volume addresses the following major topics: - Research results in observing aspects of the Arctic climate system and its processes across a range of time and space scales - Representation of cryospheric, atmospheric, and oceanic processes in models, including simulation of their interaction with coupled models - Our understanding of the role of the Arctic in the global climate system, its response to large-scale climate variations, and the processes involved.